Penggunaan Media Sosial Terutama Instagram Dalam Strategi Komunikasi Yang Efektif - Riastri Novianita; Wulan Muhariani; Cindya Yunita Pratiwi (Pascasarjana Institut Agama Islam Sunan Giri Ponorogo, 2023)
Currently, the widespread adoption of social media is evident across various age groups, encompassing children, teenagers, parents, and individuals of all ages. Social media platforms are favored not only for their user-friendliness but also for their wealth of readily available information. It is essential for users to exercise the choice of not allowing social media to overwhelm them, recognizing it as a repository of information that can be effortlessly disseminated through various online networking sites. Within moments of an event occurring, we can readily access and consume this information. The realm of communication media has seen rapid growth in tandem with advancements in communication technology. This era offers us numerous options for conveying and accessing information, whether through traditional means like print media or electronic avenues, with social media emerging as the most prominent. Social media can be defined as an online medium that empowers users to effortlessly engage, share, and generate content, including blogs, social networks (such as Facebook, YouTube, MySpace, and Twitter), wikis, forums, and virtual realms. Among these various forms, social networking stands out as the most popular choice among individuals. This platform enables users to craft personal webpages and establish connections with friends for the purpose of information sharing and communication. Among the plethora of social networks available, Facebook and Twitter have garnered the most extensive user bases, primarily due to their practicality, cost-effectiveness, and affordability.